Thursday

March 5, 2015

March 5, 2015

Posted by **John** on Sunday, April 27, 2008 at 8:30pm.

1. If f(x)=5x^3–2/x-4

find f'(x)____

what i got was (4x^2+7x-12)/x^8

2. The position function of a particle is given by s=t^3–4t^2–7t t>=0

where s is measured in meters and t in seconds. When does the particle reach a velocity of 10 m/s? ____

3. f(x)=2x^2+7x+3/ sqroot of x

Find f'(x)

i got ((x^(-1/2))(4x+7)+1/2x^(-3/2)(2x^2+7x+3))/x

- Calculus please help -
**Damon**, Sunday, April 27, 2008 at 9:10pm1. If f(x)=5x^3–2/x-4

find f'(x)____

=============================

I assume you mean

(5 x^3 -2)

----------

(x-4)

(x-4)(15 x^2) - (5 x^3-2)(1)

----------------------------

x^2 - 8 x + 16

15 x^3 -60 x^2 - 5 x^3 +2

-------------------------

x^2 - 8 x + 16

10 x^3 -60 x^2 +2

-----------------

x^2 - 8 x + 16

what i got was (4x^2+7x-12)/x^8

2. The position function of a particle is given by s=t^3–4t^2–7t t>=0

where s is measured in meters and t in seconds. When does the particle reach a velocity of 10 m/s? ____

===========================

s' = 3 t^2 - 8 t - 7 = 7

3 t^2 - 8 t -14 = 0

t = [ 8 +/- sqrt (64 +84) ] /6

= [8 +/- 12.17]/6

=3.36

==============================

3. f(x)=2x^2+7x+3/ sqroot of x

Find f'(x)

sqrt (x) (4x+7) - (2x^2 + 7 x +3)(1/2x)sqrt x

----------------------------------------

x

2 x sqrt (x)(4x+7) - (2 x^2+7x+3) sqrt x

---------------------------------------

x

(sqrt x)[8 x^2 +14 x - 2 x^2 -7 x - 3]

--------------------------------------

x

(sqrt x/x) (6 x^2 + 7 x -3)

6 x^(3/2) + 7 x^(1/2) - 3 x^-(1/2)

======================================

i got ((x^(-1/2))(4x+7)+1/2x^(-3/2)(2x^2+7x+3))/x

- Calculus please help -
**John**, Sunday, April 27, 2008 at 9:18pmI don't exactly know why but all of the answers were wrong.

- Calculus please help -
- misread this one -
**Damon**, Monday, April 28, 2008 at 1:45pm2. The position function of a particle is given by s=t^3–4t^2–7t t>=0

where s is measured in meters and t in seconds. When does the particle reach a velocity of 10 m/s? ____

===========================

s' = 3 t^2 - 8 t - 7 = 10

3 t^2 - 8 t -17 = 0

t = [ 8 +/- sqrt (64 + 204) ] /6

= [8 +/- 16.4]/6

=4.94

**Answer this Question**

**Related Questions**

Calculus- To Reiney - I have 3 calc problems that i have not been able to do ...

socials - this is the same question I posted yesterday, it is due tommorow, oh ...

english - could you please explain me how to use the following verb forms ...

To MS SUE - ''Without the English civil war, democracy would have never ...

Math - So lately in class, we've been doing stuff on finding the variables in ...

Algebra - I am in need of assistance with the following problem: v-4(4-v) = -2(...

To jhon, jackie, jill, sandra, mariam or whoever - Your posts have been removed...

English Please help - i have an essay and ive been researching the topic like ...

algebra - evaluate the expression for variables -(4h-1)/1+h;h=2 /-4b-8/+/-1-b^2...

History - 1)Why might the US have been concerned early in the war about China's ...